IMPROVING STUDENTS'SPEAKING ABILITY THROUGH ONE ACT DRAMA - Sri Yuliani (Program Studi Pendidikan Bahasa Inggris, 2020)
The aim of the study to find out whether or not it is effective to use one act drama in improving speaking ability to the eighth grade students of junior high school 44 of Palembang. The method used in this study was experimental method. The population of the study was all the eighth grade  students of junior high school 44 of Palembang consisted of 290 students. The number of sample was 74 students taken by using purposive sampling and divided into two groups namely, control and experimental. The data of test was analyzed by using t-test. The result of the study indicated that the mean of posttest in the experimental group was 69.86, and the mean of posttest in the control group was 68.33. t-obtained was 2.052 at the significance level of p> 0.05 (5%) in 2-tailed testing and degree if freedom (df) was 72, and critical value of t-table was 1.990. Since the value of t-obtained was higher than the critical value of t-table, the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It means that improving students' speaking ability through one act drama was effective.